Effect of temperature and salt on thermal inactivation of Listeria monocytogenes in salmon roe. (March 2017) - Li, Changcheng; Huang, Lihan; Hwang, Cheng-An
Abstract: Listeria monocytogenes is a potentially fatal foodborne pathogen that can be found in ready-to-eat seafood products, such as fresh salmon roe. Once contaminated, salmon roe must be decontaminated prior to human consumption. This study was conducted to determine the thermal inactivation kinetics of L. monocytogenes in raw salmon roe as affected by bacterial strain, temperature, and salt concentration. Three different strains of L. monocytogenes, including serotype 4b (F2365), 1/2b (F4260), and 1/2a (V7), were individually inoculated to salmon roe supplemented with salt (0–4.5%), and heated under different temperatures (57.5–65.0 °C) to evaluate the survival of the bacterium during heating and determine the D-values. Results showed that the thermal resistance (log D) of L. monocytogenes was significantly affected by bacterial strain, temperature, and salt and by their interactive effects, with strain F2365 being the most heat-resistant among all three strains tested. Salt added to salmon roe significantly increased the thermal resistance of the bacteria. For L. monocytogenes F2365, the z value of the bacterium in salmon roe was 5.99 °C, and its heat resistance increased with the level of salt in a linear manner. The results of kinetic analysis and the models obtained in this study may be used by the seafood industry to develop proper thermal processes to eliminate L. monocytogenes in raw salmon roe and to ensure microbial safety and prevent foodborne illness. Highlights: Listeria monocytogenes is a life-threatening foodborne pathogen. Salmon roe may be contaminated with L. monocytogenes . Thermal processing can be used to effectively inactivate L. monocytogenes . The survival of L. monocytogenes is affected by both temperature and salt. Mathematical models were developed to predict the temperature and salt on survival of L. monocytogenes .